Understanding US “Re-pivot” to Asia - Muhammad Sigit (Indonesian Journal of Peace and Security Studies (IJPSS), 2020)
This paper explains the nature and the context of the future of US foreign policy to the Asia or so-called US re-pivot policy to Asia. By using the historical method, this paper tries to make sense of US continuous engagement in Asia, past and present; with a hope to illuminate even quite distant futures of US foreign policy direction. The 2020 US presidential candidates, Donald Trump and Joe Biden have signaled their strong intention of US re-pivot to Asia. However, the new re-pivot to Asia should be different from Obama’s ‘pivot to Asia’. Re-pivot should bring practical economic, strategic, and political benefits to Asian countries, rather than simply containing China.